Images of gender arrangements of three American social organizations: a content analysis of top ranked Google images of individuals preforming organizational roles - Velasquez, Scott E. (Kansas State University, 2016)
This study explores existing beliefs and often unspoken social structural arrangements related to male privileges by examining three different, but rather important, American social organizations—the NFL, U.S. military and higher education institutions. With queries from the Google image database, I analyzed images for themes from search terms of organizations thereby tapping into the consciences of society. Since a high volume of images are produced by Google Image search, a maximum of 25 results of each search term are included as potential sources of images for this study. The primary category of non-specific gender search terms of Google images are: NFL Players, U.S. soldiers, and college students. In addition, this study also utilized a subset category of gender and sexuality specific Google search terms that are related to the primary category search terms. The subset category of gender and sexuality specific Google search terms of images are: women of the NFL, NFL gay players, U.S. female soldiers, U.S. gay soldiers, college volleyball players, and fraternity life. Both the U.S. military and the NFL presented images of men preforming competitive or aggressive activities that can be defined as masculine labors. These images are reflections of the ideal masculine male playing a special role in U.S. society—the “warrior” male. Yet most images depicted U.S, soldiers in clean combat uniform with military weapons at a ready to engage in battle. This suggests that either U.S. military have some control over images that can be displayed on popular websites. Even though page ranking software gives the appearance that popular websites are the product of algorithm but there is some evidence that ranking can be manipulated by organizations. Colleges take manipulating popular websites to another level to reach their potential clients. Unlike the U.S. military and the NFL’s search terms results that presented images of men preforming masculine activities, college students’ search term results images are images of students displaying activities that show individuals in the act of being polite and pleasant to others, as well as being supportive. I suggest that the idea behind presenting images with a feminine slant is to attract the group that is most likely to attend college after high school, which is female. College websites will most likely to have staged images of study groups and professors teaching to a small group of students. The websites featured staged images of students, in which students are almost flawless in appearance, a phenomena that could only be achieved through doctoring, cosmetics, and computer retouching. This type of images is more likely to be attractive to potential students that are searching the internet for potential colleges to attend in the future. Moreover, Photoshop images of students assist colleges and universities in controlling the images they want to introduce to potential students and media. Colleges are prudent on how much to display in images of heterosexual relationships. Most staged images that displayed heteronormativity are male and female students studying within each other personal space. It would seem that images of homosexual relationships are still taboo on college websites because there are no staged images that indicated homosexual relationship between college students. I believe that these reflections are presented as organizational websites’ marketing strategies. The marketing strategies of website designers are to implement a group think mentality of those seeking information of a specific term. This action is caused by search engine page ranking software in order to organize highly interconnected websites toward one idea thus influencing a large number of potential and current customers’ decisions. In today’s technologically connected society, societal perception of what constitutes masculinity, femininity and sexuality starts with a well-designed website. The findings will perhaps have important implications for understanding to how the negative outcomes of male privileges remain entrenched in social institutions and benefit certain segments of society at the cost of others.
Keywords: Organizational arrangements; Websites; Football; Google; Military; Higher education